Cable-Stayed Face Lift: An Innovative Short-Scar Lift for Better Correction of Nasolabial Folds in East Asians. Issue 3 (24th August 2021) - Qiu, Yajing; Gao, Wei; Yang, Jingyan; Jin, Yunbo; Zou, Yun; Qiao, Congzhen; Chen, Hui; Lin, Xiaoxi
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: The improvement of nasolabial folds by either lateral superficial musculoaponeurotic system rhytidectomy or minimal access cranial suspension lift alone is commonly performed, but patient satisfaction is often limited in East Asians. An innovative technique, termed the cable-stayed face lift, which combines the strengths of lateral superficial musculoaponeurotic system rhytidectomy and minimal access cranial suspension lift, was developed for improved results. Methods: Between 2016 and 2019, 20 cable-stayed face lifts were performed in a single hospital. Two plastic surgeons independently evaluated postsurgery outcomes using a five-point Likert scale, where 5 = excellent, 4 = good, 3 = fair, 2 = no change, and 1 = worse. Patient satisfaction was assessed by relevant items from the FACE-Q questionnaire. Results: Twenty patients with a mean age of 51 years underwent face-lift surgery. The mean follow-up ± SD was 11.3 ± 9.8 months. The five-point Likert scale score evaluated by surgeons was 3.65 ± 1.08. Patient-perceived age visual analogue scale (7.8 ± 4.4) exhibited a difference between preoperative actual age and postoperative apparent age. Patients demonstrated high satisfaction with outcome (67.5 ± 16.2) and satisfaction with lower face and jawline (76.2 ± 14.9). No major complication, hematoma, or seroma was observed. Conclusion: The authors' approach—cable-stayed face lift—offers a good alternative to provide a more effective effacement of nasolabial folds, by lifting the nasolabial folds with parallel vector and lower face and neck with the vertical vector. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.